Analisis Efektivitas Pelaksanaan Program Pendidikan Pelatihan Dalam Meningkatkan Kinerja Karyawan di PTPN IV Regional 1 Medan - Teresia Manalu, Sarah; Hutahaean, Marlan; Pasaribu, Johnson (Journal of Comprehensive Science, 2025)
The employee education and training program aims to improve skills, improve performance, improve competency capabilities, provide innovation and improve the company's image. In order for human resources to have a minimal impact on achieving the company's goals and missions, continuous quality improvement efforts must be carried out comprehensively and sustainably. One way to improve the quality of human resources is through education and training. The research method used by researchers is the Qualitative research method. This study attempts to examine the effectiveness of the implementation of education and training programs in improving employee performance at PTPN IV Regional 1 Medan. The results of this study indicate that this education and training are very useful and appropriate for employee needs. Because with this education and training to help employees in carrying out their duties, in addition to increasing employee competency capabilities, it creates a productive and growth-oriented work environment. This is reflected in the employee performance assessment carried out annually.